Pengaruh Audit Tenure, Ukuran Perusahaan, dan Audit Delay terhadap Kualitas Audit - Nurgina, Shafa Adinda; Nurmalina, Rina (Indonesian Accounting Literacy Journal, 2024)
Audit quality is the probability and willingness of an auditor to detect fraud in the client's accounting system and report deviations that occur. This study aims to examine the influence of external factors that can affect audit quality, namely audit tenure, company size, and audit delay, in companies within the transportation infrastructure and heavy construction and civil engineering sub-sectors listed on the IDX for the years 2020-2022. This research is quantitative in nature, with a population of 34 companies. The sample was determined using purposive sampling, resulting in 84 samples from 28 companies. The research method used is logistic regression analysis with SPSS 27. The results show that audit tenure has a positive and significant effect on audit quality, while company size and audit delay do not affect audit quality. Furthermore, audit tenure, company size, and audit delay collectively influence audit quality.